Phenotypic performance of Srikayang's shallot variety M1 by colchicine induction - ANNISA ADELIA NUR RAHMAWATI; NANDARIYAH NANDARIYAH; PARJANTO PARJANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Rahmawati ADN, Nandariyah, Parjanto. 2024. Phenotypic performance of Srikayang's shallot variety M1 by colchicine induction. Biodiversitas 25: 1297-1303. Srikayang shallot is one of the shallot varieties from Kulonprogo Yogyakarta, and it has relatively small bulbs. Indonesian consumers prefer shallot, which has dense bulbs, is large (diameter ? 2.5 cm), has a spicy taste, and is fragrant. The efforts to increase shallot's diversity are important. This study aimed to evaluate the performance of Srikayang shallot M1 and evaluate Lethal Doses (LD50) of colchicine. This research was conducted from September to November 2023 at Balecatur Planting Garden, Yogyakarta. Srikayang shallot bulbs were used, and colchicine concentration consisted of 0%, 0.05%, 0.075%, and 0.1%, with a soaking period of 3, 6, and 12 hours. The study was conducted using a randomized block design (RBD). Data were analyzed using descriptive analysis and probit analysis. The colchicine concentration and soaking duration affected the morphological character of Srikayang plants in leaf color, bulb skin color, bulb shape, bulb neck shape, and root tip shape. This study showed that the interaction of colchicine concentration and soaking duration improved variability on plant height, number of leaves, number of saplings, bulb weight in the cluster, main bulb weight, and main bulb diameter. The LD50 of Srikayang shallots was obtained at a colchicine concentration of 0.065%.